2018
DOI: 10.7567/1882-0786/aaeede
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation of AlN film using two-dimensional multilayer hexagonal BN for deep-ultraviolet light-emitting diodes

Abstract: Crack-free crystalline AlN film was synthesized on two-dimensional multilayer hexagonal BN (h-BN) by metal organic vapor phase epitaxy (MOVPE). The multilayer h-BN was directly grown on sapphire substrates in wafer scale by MOVPE, with a thickness of 2.9 nm. The AlN film grown on the h-BN/sapphire presented a smooth surface. We further realized the exfoliation of AlN film utilizing the weak bonds within h-BN layers. Moreover, the AlGaN-based deep-ultraviolet light-emitting diodes grown on the AlN/h-BN/sapphire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…[1] Besides, Wu et al reported the growth of AlGaN-based deep-ultraviolet LED structure on oxygen-plasma-treated h-BN/Al 2 O 3 . [30] Although several groups have reported the epitaxy of III-nitrides on h-BN, graphene, and so on, the interface bonding behaviors and/or the nucleation phenomena of III-nitrides are seldom reported and are not well studied to the best of our knowledge. [31][32][33] In this work, we study the epitaxy of GaN on 2-in.…”
Section: Doi: 101002/advs202000917mentioning
confidence: 99%
“…[1] Besides, Wu et al reported the growth of AlGaN-based deep-ultraviolet LED structure on oxygen-plasma-treated h-BN/Al 2 O 3 . [30] Although several groups have reported the epitaxy of III-nitrides on h-BN, graphene, and so on, the interface bonding behaviors and/or the nucleation phenomena of III-nitrides are seldom reported and are not well studied to the best of our knowledge. [31][32][33] In this work, we study the epitaxy of GaN on 2-in.…”
Section: Doi: 101002/advs202000917mentioning
confidence: 99%
“…They observed blue electroluminescence from those LEDs on a transferred metal foil. Wu et al grew crack‐free AlN layers on h ‐BN/Al 2 O 3 substrates with O 2 plasma treatment and confirmed a DUV emission from AlGaN LEDs …”
Section: Introductionmentioning
confidence: 95%
“…In this respect, wafer‐scale thin‐film growth methods, such as CVD or molecular beam epitaxy (MBE), are preferable to realize device applications. Many research groups have reported thermal CVD of BN thin films with a wide variety of boron precursors, such as borazine (B 3 N 3 H 6 ), boron‐halides (BF 3 , BCl 3 , and BBr 3 ), and triethyl boron ((C 2 H 5 ) 3 B, TEB), on sapphire, SiC, Ni, and Cu substrates. For borazine, it is difficult to control the N/B ratio, which leads to turbostratic boron nitride ( t ‐BN), a disordered phase of h ‐BN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many research groups have reported BN growth by thermal chemical vapor deposition (CVD), plasma‐assisted CVD, and molecular beam epitaxy (MBE) . The growth conditions include a wide varieties of boron precursors of borazine (B 3 N 3 H 6 ), boron halides (BF 3 , BCl 3 , BBr 3 ), triethylboron ((C 2 H 5 ) 3 B, TEB), trimethylboron ((CH 3 ) 3 B, TMB), and diborane (B 2 H 6 ) . Also, various substrates for BN growth were investigated, such as sapphire, SiC, Ni, and Cu …”
Section: Introductionmentioning
confidence: 99%